Analysing euro area inflation outlook with the Phillips curve - Sami Oinonen; Lauri Vilmi (Bank of Finland, 2021)
This paper presents the New Keynesian Phillips Curve (NKPC) -based framework for analysing euro area inflation outlook. Our NKPC specification, that relies on market- and survey-based inflation expectations, explains well euro area inflation dynamics. Its forecasting performance is also comparable to the performance of the ECB's official forecasts in both short- and long-horizons. Overall, the NKPC is a useful tool for monitoring euro area inflation outlook. Thanks to its fast and light updating procedure it provides almost real-time information on inflation outlook.
urn:nbn:fi:bof-202109081419
Keywords: E31; E37; 330; euro area; inflation expectations; inflation forecasting; Phillips curve